Evaluation of Back Extrusion Test Precision and Sensitivity for Cooked Germinated Brown Rice Texture Measurement in Production Process - Kannapot Kaewsorn; Pisut Maichoon; Pimpen Pornchaloempong; Warawut Krusong; Panmanas Sirisomboon; Munehiro Tanaka; Takayuki Kojima (My University, 2023)
The texture properties of cooked rice are a dominant property which can indicate the eating quality. Evaluation of back extrusion (BE) test precision and sensitivity for cooked germinated brown rice (GBR) texture in production process was investigated in this study. BE test on texture properties of cooked GBR rice show high precision of measurement of hardness, toughness and stickiness tests which indicated by the repeatability and reproductivity test but the sensitivity indicated by coefficient of variation of the texture properties. The findings of the study of the effect of different soaking and aging duration in the production of Khao Dawk Mali 105 (KDML 105) GBR on cooked GBR texture measured by BE test confirmed the developed protocol for evaluation of high precision and sensitivity of the texture measurement method. Repeatability and reproducibility of reliable measurements have a low standard deviation of the farthest different between replicates, which is considered high precision. High coefficient of variation where the relative wide variation of the absolute value of the property can be detected indicate high sensitivity which even small resolution can be detected or vice versa. But the correlation coefficient among the texture properties by BE were not related to the precision or sensitivity of the test. By these results, the original protocol for determination of precision and sensitivity of food texture measurement was successfully verified as the usable evaluation protocol for GBR texture measurement.
Keywords: Repeatability; Texture (cosmology); Coefficient of variation; Accuracy and precision; Food composition and properties